Peripapillary changes after vitrectomy and silicone oil tamponade for rhegmatogenous retinal detachment - Jian Jiang; Rui Li; Jin-Xiu Zhou; Rui-Mei Li; Rui-Hua Wang; Xia-Ping Wang; Ran Dou; Ya-Ding Jia; Shuang-Nong Li; Song Chen (Indian Journal of Ophthalmology, 2021)
Purpose: To evaluate the peripapillary changes after vitrectomy and silicone oil (SO) tamponade in eyes with rhegmatogenous retinal detachment (RRD). Methods: In this study, 25-gauge vitrectomy with SO tamponade was performed in 22 eyes with RRD. The radial peripapillary capillary (RPC) vessel density (VD) and retinal nerve fiber layer thickness (RNFLT) were assessed by optical coherence tomography angiography at 2, 4, 8, and 12 weeks postoperatively. The values of healthy fellow eyes were used as controls. Results: The global RPC VDs were significantly lower in the eyes with RRD than in fellow healthy eyes at 2 weeks (P < 0.001), and increased at 4 weeks, then decreased over time after surgery (F = 1.046, P = 0.377). The RPC VDs in the superior-hemifield were lower than those in the inferior-hemifield at 12 weeks postoperatively (t = −2.844, P = 0.010). The global RNFLTs decreased gradually after vitrectomy in the eyes with RRD (F = 1.312, P = 0.276). The RNFLTs in the superior-hemifield were thinner than those in the inferior-hemifield at 12 weeks postoperatively (t = −2.222, P = 0.037). The global, superior, and inferior RNFLTs were correlated with corresponding RPC VDs in the eyes with RRD at all time-points postoperatively (P < 0.05). Conclusion: RRD resulted in the decrease of RPC VDs. The RPC VDs recovered in the early postoperative period but were still lower than the normal level. Long-term application of SO tamponade resulted in the reduction of peripapillary VDs secondary to loss of RNFLTs.